PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DENGAN DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING - Tazkia Nilnal Muna; Ristanti Akseptori; Arfiana Dewi (Proceeding Maritime Business Management Conference, 2024)
This study aims to determine the effect of work environment on employee performance through work discipline at one of the shipyard companies in Surabaya. The company faces performance problems that are thought to be caused by a less structured work environment. This study aims to analyze how these factors affect performance through work discipline. This study used questionnaires and interviews to collect data from 136 employees through simple random sampling. Instrument quality assessment was carried out using the outer model test, while hypothesis testing was carried out through the inner model method. The results showed that the work environment has a positive effect on employee performance. The work environment does not have a positive effect on work discipline. Work discipline is not proven to have a positive influence between employee performance and work environment variables. These results indicate the importance of improving the work environment to improve employee performance.